The Correspondence of Elizabeth Butler, Duchess of Ormonde: edited by Naomi McAreavey, Renaissance English Text Society, 40, New York and Toronto: Iter Press, 2023, 440 pp., $79.95, ISBN 9781649590183. - Gregg, Hannah (Women's Writing, 2023)
In I The Correspondence of Elizabeth Butler, Duchess of Ormonde i , Naomi McAreavey allows her reader to delve into the life of a previously understudied female noble who held considerable influence across both English and Irish society. McAreavey provides the first book-length study of the Duchess of Ormonde and her extant letter collection, which comprises over three hundred letters spanning six decades - starting in the 1630s and extending up until her death in 1684.